Relatório de estágio técnico profissional em medicina veterinária: sanidade, clínica e cirurgia dos animais de produção - Roehrig, Guilherme Diego (2023)
The Professional Technical Internship (ETP) was carried out in the area of ​​health management, clinic and surgery of production animals, under the academic guidance of Prof. Me. Jerbeson Hoffmann da Silva, in the municipality of Tupandi in the state of Rio Grande do Sul, from July 25, 2023 to October 23, 2023, totaling 530 hours. The ETP allowed the acquisition of essential skills to diagnose, treat and prevent problems found in animals from different properties. Through this internship opportunity, it was possible to always seek the best solution for each case, always aiming for the well-being and health of the animals. Furthermore, the internship brought the opportunity to dialogue with producers, as communication is essential for successful work as a Veterinarian. This conversation allowed us to better understand the needs of producers, contributing to good personal and professional development. The professional technical internship brings the importance of associating the theoretical knowledge acquired during the Veterinary Medicine course with practical activities carried out on a daily basis, being essential to train qualified professionals prepared to experience the challenges of the veterinary field.